Positive Character Formation Strategy Through Gadgets (Study of Semester I and III Students of the Islamic Guidance and Counseling Study Program) - Ira Wirarti; Addin Haris Perdana (Jurnal Studi Guru dan Pembelajaran, 2024)
Research and abstract title search made easy with these keywords. This research aims to find strategies for forming positive characters through gadgets. This research used a mixed-method study with a psychodynamic approach to identify the negative influence of gadgets on 100 first and third-semester students at the North Sumatra State Islamic University, Medan. A census sampling method focused on self-defense, personality development, emotions, and individual motivations regarding gadget use. Data was obtained through questionnaires and referring to literature reviews. Data analysis involves pre-analysis testing, hypothesis testing, data reduction, data presentation, and conclusions. The research results show that the use of gadgets has a negative impact, especially related to dependence and mental health disorders. Strategies for forming positive character through individual awareness, the role of the family, the wise use of technology, social participation, and inter-institutional cooperation are essential. The Healthy Gadget Movement is suggested as a critical initiative with increased awareness and collaboration between the government, educational institutions, and the technology industry, as well as integrating digital literacy into the curriculum. Parental support and ongoing evaluation are the keys to the success of this movement in creating a society that can use gadgets healthily and positively.